Perancangan Sistem Marketplace Penyedia Jasa Pangkas Rambut Berbasis Website Menggunakan Mern Stack - Aldi Nugraha; Rakhmat Dedi Gunawan; Fenty Ariany (PT. SNN MEDIA TECH PRESS, 2023)
Since covid 19, many barbershops have opened home call services to increase consumer convenience as well as competitiveness, so reservations are provided via telephone or whatsapp calls. While serving call services, there are several problems that make consumers feel disappointed, such as the difficulty of knowing the status of the captain, consumers have to confirm repeatedly to find out whether the barber is available or not for home calls. To anticipate these problems, a marketplace system for barbershop service providers was created to help estimate capster work time to be more efficient using extreme programming methodology and web-based Mern Stack technology which can later be used by barbershop service providers to manage their barbershop or barbershop, as well as manage the work status of the capster, so that consumers can find out the work status of their subscription capster. The calculation results from testing the marketplace system for barber service providers using ISO 25010 resulted in a percentage of 99% for the functionality and usability aspects resulting in a percentage of 85.6%, in this case indicating that the developed system runs as expected and there are no bugs in it.